Antipsychotic medications and sleep problems in patients with schizophrenia - Cederlöf Erik; Holm Minna; Taipale Heidi; Tiihonen Jari; Tanskanen Antti; Lähteenvuo Markku; Lahdensuo Kaisla; Kampman Olli; Wegelius Asko; Isometsä Erkki; Kieseppä Tuula; Palotie Aarno; et al. (Elsevier, 2025)
Background: Sleep problems are common and related to a worse quality of life in patients with schizophrenia. Almost all patients with schizophrenia use antipsychotic medications, which usually increase sleep. Still, the differences in subjective sleep outcomes between different antipsychotic medications are not entirely clear.
Methods: This study assessed 5466 patients with schizophrenia and is part of the nationwide Finnish SUPER study. We examined how the five most common antipsychotic medications (clozapine, olanzapine, quetiapine, aripiprazole, and risperidone) associate with questionnaire-based sleep problems in logistic regression analyses, including head-to-head analyses between different antipsychotic medications. The sleep problems were difficulties initiating sleep, early morning awakenings, fatigue, poor sleep quality, short (≤6 h) and long sleep duration (≥10 h).
Results: The average number of antipsychotic medications was 1.59 per patient. Clozapine was associated with long sleep duration (49.0 % of clozapine users vs 30.2 % of other patients, OR = 2.05, 95 % CI 1.83-2.30, p < .001). Olanzapine and risperidone were in head-to-head analyses associated with less sleep problems than patients using aripiprazole, quetiapine, or no antipsychotic medication. Aripiprazole and quetiapine were associated with more insomnia symptoms and poorer sleep quality. Patients without antipsychotic medications (N = 159) had poorer sleep quality than patients with antipsychotic use, and short sleep duration was common (21.5 % of patients using antipsychotics vs 7.8 % of patients using antipsychotics, OR = 2.97, 95 % CI 1.98-4.44, p < .001).
Conclusions: Prevalence of sleep problems is markedly related to the antipsychotic medication the patient uses. These findings underline the importance of considering and assessing sleep problems when treating schizophrenia patients with antipsychotics.